Modern Monetary Theory: a criticism from the periphery - Vergnhanini, Rodrigo; De Conti, Bruno (Brazilian Keynesian Review, 2018)
This paper presents the recent debate on modern monetary theory (MMT) and contributes to a critical view on its application to peripheral countries. MMT has been centered on both demystifying postulates of the ‘New Macroeconomic Consensus’ and offering an alternative theory to reach full employment with price stability. However, it has been criticized for assuming that constraints on domestic policies are generally self-imposed, not arising from international markets. Using the “international currency hierarchy” approach, this paper argues that peripheral countries, in the context of financial globalization, are not fully sovereign in determining its own macroeconomic policy. Our main argument is that currencies issued by peripheral countries do not fulfill money classical functions at the international level. Being hence illiquid at the international scenario, these peripheral currencies (and assets) are demanded by the international investors only in the quest for high returns; moreover, this demand depends on the “international liquidity preference” and the markets’ confidence in this country. Consequently, interest rates in peripheral countries tend to be higher and volatile. Additionally, the exchange rate is potentially under the pressure of this capital flows movements. Finally, monetary, fiscal and exchange policies in peripheral countries have constrains that are not considered by MMT.